Musical Spaces : Place, Performance, and Power - Horlor, Samuel; Williams, James (Jenny Stanford Publishing, 2022)
There is growing recognition and understanding of music's fundamentally spatial natures, with significances of space found both in the immediacy of musical practices and in connection to broader identities and ideas around music. Whereas previous publications have looked at connections between music and space through singular lenses (such as how they are linked to ethnic identities or how musical images of a city are constructed), this book sets out to explore intersections between multiple scales and kinds of musical spaces. It complements the investigation of broader power structures and place-based identities by a detailed focus on the moments of music-making and musical environments, revealing the mutual shaping of these levels. The book overcomes a Eurocentric focus on a typically narrow range of musics (especially European and North American classical and popular forms) with case studies on a diverse set of genres and global contexts, inspiring a range of ethnographic, text-based, historical, and practice-based approaches.